2015
DOI: 10.1111/sms.12436
|View full text |Cite
|
Sign up to set email alerts
|

Impact‐induced muscle damage and urinary pterins in professional rugby: 7,8‐dihydroneopterin oxidation by myoglobin

Abstract: Muscle damage caused through impacts in rugby union is known to increase oxidative stress and inflammation. Pterins have been used clinically as markers of oxidative stress, inflammation, and neurotransmitter synthesis. This study investigates the release of myoglobin from muscle tissue due to force-related impacts and how it is related to the subsequent oxidation of 7,8-dihydroneopterin to specific pterins. Effects of iron and myoglobin on 7,8-dihydroneopterin oxidation were examined in vitro via strong catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…The concentrations observed following each of the mixed martial arts events suggest that a training session is of greater intensity than a simulated contest, most likely a result of the difference in duration. Moreover, it is comparable to other 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 high-impact sports that have shown similar changes in urinary myoglobin [4,5], which demonstrate the severity of the sport that has been widely neglected in exercise research. Detection of myoglobin at an absorbance of 400 nm produced a clear visible peak with no observed tailing or interference from neighboring urinary analytes allowing for clear interpretation, whereas the dilution in 10 mM ammonium acetate (pH 7.0) seemed to alleviate any stabilization concerns that had been previously noted over a 24-h period [14].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The concentrations observed following each of the mixed martial arts events suggest that a training session is of greater intensity than a simulated contest, most likely a result of the difference in duration. Moreover, it is comparable to other 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 high-impact sports that have shown similar changes in urinary myoglobin [4,5], which demonstrate the severity of the sport that has been widely neglected in exercise research. Detection of myoglobin at an absorbance of 400 nm produced a clear visible peak with no observed tailing or interference from neighboring urinary analytes allowing for clear interpretation, whereas the dilution in 10 mM ammonium acetate (pH 7.0) seemed to alleviate any stabilization concerns that had been previously noted over a 24-h period [14].…”
Section: Discussionsupporting
confidence: 74%
“…Feinfeld and coworkers [9] observed patients with acute rhabdomyolysis exceeding concentrations of 1 mg/ml, whereas previous studies have suggested that patients with values exceeding 20 mg/ml are at more of an increased risk of decreased renal function [21,27]. In addition, values as high as 32.9, 410, and 3000 mg/ml have been observed following crush trauma [3], strenuous military training [13], and myocardial infarction [2], respectively, whereas values reaching 52 and >100 mg/ml have been observed in competitors following a marathon [28] and professional rugby [5], respectively. Therefore, in an exercise and/or serious trauma scenario where muscle damage is expected to rise significantly, this assay may provide the most cost-effective and operator-friendly option for simple and rapid quantitation for both small and large cohorts suffering mild to severe skeletal muscle stress in a range that is widely accepted as "clinically relevant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The advantage of chromatography is the simultaneous determination of creatinine with the analyte that requires creatinine correction. Usually analysed at 234 nm by ultra-violet detection, the method has been used effectively in the quantification correction of neopterin [26,240,241], desmosine [242], catecholamines, and metanephrines [243].…”
Section: Creatininementioning
confidence: 99%
“…The extremely rapid elimination kinetics of myoglobin [278] in comparison to more commonly utilised plasma markers such as creatine kinase [279,280] make it an ideal biomarker that provides an immediate evaluation of severity. It has been used extensively in several forms of exercise [20,240,241,[281][282][283][284][285] and is quantifiable using both ELISA [241] and reverse-phase high performance liquid chromatography (RP-HPLC) [284].…”
Section: Myoglobinmentioning
confidence: 99%